Seasonal Variations in the Haematological Values of the Nigerian Duck (Anas platyrhynchos) - Olayemi, F.O.; Arowolo, R.O.A. (International Journal of Poultry Science, 2009)
The effects of dry and wet seasons on the blood profiles of the Nigerian duck were determined. This is with a view of elucidating any seasonal variations in these parameters. The haematological values studied included the erythrocyte values (RBC, PCV, Hb., MCH, MCHC and MCV) and the leucocyte values (total and differential leucocyte counts). In the dry season, the duck had higher (p